REACTIONS OF FIRST YEAR MEDICAL STUDENTS IN THE DISSECTION ROOM, WITH PROSECTED CORPSES, AND THE INCIDENCE ON OWN BODY DONATION. Las reacciones de los estudiantes de primer año de Medicina en la sala de disección, con cuerpos disecados, y la incidencia sobre la donación del propio cuerpo - Susana N. Biasutto; Isaías E. Molina Vargas; Diego M. Weigandt; M. Valentina Mora; Ramiro A. A. Vargas; Atilio J. Bertocchi Valle; M. Florencia Uanini; Oscar P. David; Daniel Urrutia; Marcos A. Spinelli; Manuel N. J. Olivera; Maximiliano Giménez; et al. (Asociación Argentina de Anatomía Clínica, 2019)
Student's perceptions in the dissection-room and the relationship with the teaching staff determine their affinity with Anatomy and their introduction in the medical career. Our objective was to evaluate three different instances of the relation student/dissection-room during the Anatomy course, the importance students assigned to the corpses, symptoms and emotions associated to the dissection-room, their causes and also participants' attitudes to the own body donation. Three surveys: initial perception, reactions by the first contact with the corpses and further evolution were performed to 237 first year students. Sixty three per cent were women and 97% argentine, of whom 59% were from Cordoba province and the rest for nearly all the country provinces. Hundred per cent considered very important Anatomy for the career and corpses for Anatomy. For 91% dissection should be compulsory for first year medical students. Most often physical reactions were ocular and nasal irritation, while the most frequent emotions were enthusiasm and surprise, due mainly to corpse and dissection-room smell.  Coping strategies to those reactions were: to focus on the topic, to watch the corpse as an object, to relax, humor and others. The will to donate the own body varied from 57% to 49% and 52%. Those percentages were not statistically different (p=0.1606), but higher than others in the literature. Influence of the corpse exposition on the attitude to donation seems to be less important than other articles; probably because our students do not dissect by themselves or because they recognize a great need of corpses.   La percepción de los estudiantes en la sala de disección y su relación con el equipo docente determina su afinidad con la Anatomía y la introducción en la carrera médica. Nuestro objetivo fue evaluar tres diferentes instancias de la relación estudiante/sala de disección durante el curso de Anatomía, la importancia que los estudiantes asignan a los cuerpos, los síntomas y emociones asociados a la sala de disección, sus causas y las actitudes de los participantes hacia la donación del propio cuerpo. Se realizaron 3 encuestas: percepción inicial, reacciones ante el primer contacto con el cadáver y evolución posterior, en 237 estudiantes de primer año. El 63% eran mujeres y 97% argentinos, de los cuales el 59% provenían de la provincia de Córdoba y el resto de casi todas las provincias del país. Cien por ciento consideraron muy importante la Anatomía para la carrera y los cuerpos para la Anatomía. Para el 91% la disección debería ser obligatoria para los estudiantes de primer año de Medicina. Las reacciones físicas más comunes fueron la irritación ocular y nasal, mientras que las emociones más frecuentes fueron entusiasmo y sorpresa, debidas principalmente al olor de los cuerpos y de la sala. Las estrategias usadas para afrontar estas reacciones fueron: enfocarse en el tema, ver el cuerpo como un objeto, relajarse, humor y otros. La voluntad de donar el propio cuerpo varió de 57% a 49% y 52%. Estos porcentajes no fueron estadísticamente diferentes (p=0,1606), pero mayores que otros en la literatura. La influencia de la exposición a los cuerpos sobre la actitud hacia la donación parece menos importante que en otros artículos; probablemente porque nuestros estudiantes no disecan por sí mismos o porque reconocen la gran necesidad de cuerpos.